Unlocking the Relationship Between Digital Age's and Spirituality's Potential: A Review - Geetika Gulati; Arvita Chandail; Puja Suri; Sangeeta Kakkar (International Journal of Trends in Humanities, 2025)
Aim: The purpose of this review was to explore how spiritual practices are changing in a society that is more connected by digital means. The study intends to examine the ways in which digital platforms—such as online communities, virtual prayer services, and meditation applications—allow people to interact with spirituality in fresh and approachable ways. Methodology: This qualitative study incorporated previous ten years research and digital case studies with the help of Google scholar, PubMed, Shodh Ganga. Findings: The results suggested that digital platforms facilitate easier access to spiritual materials, enabling people to engage with larger groups and remotely pursue their own spiritual development. But the emergence of digital spirituality also brings with it new ethical challenges, such worries about virtual practices' authenticity, privacy, and the commercialization of spiritual content. Conclusion: The study concluded by emphasising that there is necessity for a well-rounded strategy in which technology improves spiritual well-being without sacrificing moral standards. Implication: This study provides recommendation on how to use the digital world in a way that supports psychological health and is consistent with one's own spiritual beliefs
Keywords: Ethical issues; digital era; psychological health; spirituality; technology